Joyful Learning Berbasis Objek Wisata Flores: Sebuah Upaya Kreatif untuk Menstimulasi English Speaking Skills Siswa - Agustina Pali; Agnes Remi Rando (Universitas Pahlawan Tuanku Tambusai, 2022)
The learning process is one of the upstream factors that contribute to learning outcomes. For this reason, teachers’ creativity is needed in this process because teachers’ creativity can affect the level of students’ success. This study aims to determine the significance of teachers’ creativity through the Joyful learning approach based on Flores tourism in stimulating English speaking skills of 29 fourth grade elementary school students at SD GMIT Ende 4. The data were collected through observation, interviews, tests and documentation. The data were then analyzed using qualitative descriptive analysis techniques. The results of the analysis showed a significant increase in the value of speaking skills in the subjects studied in each cycle of action. The percentage increase from pre-test to cycle 1 was 73.5%, while the percentage increase from cycle 1 to cycle 2 was 84.8%. Thus, it can be concluded that the Joyful Learning approach based on Flores tourism objects can be used as a creative and innovative effort that is feasible to be applied in speaking classes because it can improve students' speaking skills.